Optical Coherence Tomography Biomarkers in Predicting Treatment Outcomes of Diabetic Macular Edema After Dexamethasone Implants - Huang, Yu-Te; Chang, Yen-Chieh; Meng, Ping-Ping; Lin, Chun-Ju; Lai, Chun-Ting; Hsia, Ning-Yi; Chen, Huan-Sheng; Tien, Peng-Tai; Bair, Henry; Lin, Jane-Ming; Chen, Wen-Lu; Tsai, Yi-Yu (Frontiers in Medicine, 2022)
Purpose: To identify OCT biomarkers that may predict functional and anatomical outcomes in diabetic macular edema (DME) patients treated with intravitreal dexamethasone (DEX) implant. Materials and Methods: Sixty-four eyes from 50 PDR patients with DME were enrolled. Best-corrected visual acuity (BCVA) and OCT biomarkers including central retinal thickness (CRT), subretinal fluid (SRF), intraretinal cysts (IRC), ellipsoid zone disruption (EZD), disorganization of retinal inner layers (DRIL), hard exudate (HE), hyperreflective foci (HRF), epiretinal membrane (ERM), and vitreomacular interface (VMI) changes were evaluated at baseline and at 3, 6, and 12 months after treatment. Multiple logistic analysis was performed to evaluate each OCT biomarker as a predictive factor for functional and anatomical improvement at the end of treatment. Results: The presence of SRF at baseline was associated with a favorable outcome, with CRT improving by more than 100 μm after treatment from multivariate logistic regression analysis (odds ratio 6.16 (1.75-21.6)) In addition, baseline SRF predicted a greater CRT improvement from multiple regression analysis (model R-square 0.11, p=0.006). The reduction of DRIL, SRF, LONLC, IRC, and EZD were correlated with better CRT improvement (more than 100μm) (P<0.05). SRF and EZD recovery can also predict better visual prognosis (P<0.05). Conclusion: OCT biomarkers can be used to predict DME patients who may benefit the most after DEX treatment. We suggest that the DEX implant should be considered as a first line treatment in DME patients with SRF.